“The Indian Struggle Against Predatory Journals: The Importance Of Quality Control” (Journal of Pharmaceutical Negative Results, 2023)
We hear the expression "Publish or perish" all the time these days in the scientific community. The most significant indicator of a researcher's advancement or prowess in their specific fields, whether they are a rookie researcher or an experienced expert, is their publishing metrics. The initial purpose of publishing a scientific paper was to share your groundbreaking discoveries regarding a particular ailment with the rest of the world. Every article was intended to provide an appropriate research question's solution and raise a few more for additional investigation. However, this has become a never-ending "rat race" of publication metrics rather than highquality research due to the pressures of "publish or perish." Publications are used to evaluate your success at various levels, not your worth or your desire to make a difference in the community. Publications are a significant factor of student achievement, selection in job interviews, promotions, and other outcomes. As a result, our discipline is in a wild rush to publish new work. The emphasis is on the publications that a research project can produce, not on the validity of the study or the outcomes of the research. Publication is the main goal of doing a research project. A research effort is deemed unsuccessful if it does not produce any publications. The goal of the current study was to determine which category of educational and research institutions in India publishes the majority of their work in predatory open access journals and to ascertain whether academicians in India are aware of these publications